Ser Brahmeiro: práticas identitárias e discursivas no Hot Site da Brahma Z - Figueiredo, Débora de (2009)
The online advertising has been highlighted by exploring one of the main characteristics of new media: interactivity. The temporary promotional sites, better known as hotsites become a strong tool in the advertising cybermedia, for providing cases of interaction involving the internet. In the space of digital hotsites there are spaces that can simulate the internet, interact, test, build "new" identities for themselves and for others and, if desired, can even buy the product in focus in hotsite. The process of interactive simulation and creates a state of pleasure, freedom and power to act as the will of the internet, which is led by trick online. The hotsites became a stronghold of plural information, construction of brand identity and consumer of the product in promotion in promopages. All this process is mainly by means of discursive practices and identity that (re) signify and promote a number of changes affecting social relations, economic, cultural and ideological, providing an interaction with the Internet site itself and with other Internet users. Such practices have become part of day-to-day for all who access sites in the network, to integrate with the world hypermodern, hotsites represented in the new, the speed, the consumption and the market logic. The ways these practices happen to change way of thinking and acting of people in agony of transformation and change of reality, see the interaction the possibility of a "new" identity, which aplaque all the anxiety resulting from hypermodern life. It should be trying to understand how this process works and what its consequences and its effects of meaning. This dissertation aims to identify and analyze the discursive practices and identities that emerge in the interaction with the Brahma hotsite Z. The theoretical analysis of French speech and Foucaultian ideas are fundamental in this work. Also contribute to the reflection scholars in the field of history, communication, sociology, and new technologies such as Foucault (1986,1987,1996 ) for the discursive practices and identities, Bauman (1998,2001,2005) and Lypovetsky (1989.2004, 2007) to the question of identity in hipermodernidade, Lemos (2004.2006) and Lévy (1996.1999) in respect of cyberculture and the internet and Carvalho (1996 ) and Pine (2000) for questions about advertising. The body of research is composed of the Brahma hotsite Z (http://www.brahma.com.br) that was online during the september 2007 and (http://www.soubrahmeiro.com.br/index . aspx) which is currently online. In the analysis we could observe the interaction between the identities and what are these spaces. Through metaphors, paradoxes and ironies in the advertising discourse, the interlocutor is led to participate in games of interaction, feeling part of the site and all guile offered online. It is thus the subject "Brahmeiro," characterized as a consumer battle, warrior, promoter of the union family, independent, confident and responsible.